Understanding cultural participation through participation – inventiveness, multivalence and epistemic modernisation. Issue 1 (1st January 2020) - Stage, Carsten; Eriksson, Birgit; Reestorff, Camilla Møhring
ABSTRACT: This article analyses the methodology of the "Reccord" research project, which had the dual ambition of (1) being participatory and (2) studying cultural participation within a specific type of under-researched cultural institution in which participation is frequently stressed as a key objective: cultural centres. To address how the methodology is understood as participatory, the article outlines five existing definitions of "a participatory methodology" – based on co-creation, co-decision, local project-building, empowerment and issue construction – and discusses to what extent these definitions can be used to understand the research setup and process, which was based on 20 exchange and data collection visits performed by cultural centre employees across Europe. The article argues that this kind of participatory research experiment is interesting for researchers and their cultural partners as it stresses inventiveness, creates a focus on multivalent research outcomes, and engages cultural institutions and workers in processes of epistemic modernisation .